Principal Component Analysis – A Realization of Classification Success in Multi Sensor Data Fusion - Masnan, Maz Jamilah; Zakaria, Ammar; Shakaff, Ali Yeon Md.; Mahat, Nor Idayu; Hamid, Hashibah; Subari, Norazian; Saleh, Junita Mohamad (IntechOpen, 2012)
None